ANALYSIS OF MARKETING EFFICIENCY OF OIL PALM FRESH FRUIT BUNCHES IN INDEPENDENT SMALLHOLDERS IN LANDAK REGENCY - Sinaga, Hesiana Yarli; Josua Parulian Hutajulu; Shenny Oktoriana (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2025)
West Kalimantan as the fourth largest palm oil producing province in Indonesia, as much as 42.3% of palm oil plantations belong to smallholder plantations. One of the villages in West Kalimantan is Taas Village where the majority of the population manages palm oil plantations. However, farmers in Taas Village tend to get a fairly low purchase price compared to other villages. Therefore, it is necessary to conduct a marketing channel analysis in order to choose an efficient marketing institution to sell their palm oil FFB. In addition, independent palm oil farmers must also be more careful and wise in dealing with existing price changes. The purpose of this study is to 1) Analyze the marketing channels of fresh fruit bunches of independent palm oil farmers. 2) Analyze the marketing margin and percentage of price share (farmer's share) received by independent palm oil farmers. 3) Analyze the level of efficiency of marketing Fresh Fruit Bunches (FFB) carried out by independent palm oil farmers.The population involved in this study is all oil palm producers who are alreadyproducing, as well as institutions involved in FFB marketing. Farmer samples were selected through random sampling while the selection of traders, RAM and PKS samples used the snowball sampling method. Data from 45 informants was analyzed quantitatively using the formula of marketing margin, farmer's share, and marketing efficiency.The findings of the study show that there are three FFB marketing channels in Taas Village. Marketing Channel I is: Farmers – collector traders – PKS. Channel II is: Farmers – Collector traders – RAM – PKS. Channel III is: Farmers – RAM – PKS. These three marketing channels are efficient based on the results of data analysis because FS > MP, with FS > 50%.